How did parents' experiences in the labour market shape children's social and emotional development during the pandemic? - Sarah Cattan; Christine Farquharson; Sonya Krutikova; Andrew McKendrick; Almudena Sevilla (Institute for Fiscal Studies (IFS), 2023)
The COVID-19 pandemic disrupted many aspects of children's lives, with impacts on their social and emotional development as well as their educational attainment. School closures increased social and emotional difficulties (Blanden et al., 2021); lack of contact with friends and extended family left some children without a trusted adult to turn to (Newlove-Delgado et al., 2021); and severe illness and death of loved ones increased (Slomski, 2021; Liang, Becker and Rice, 2022). In this report, we consider another channel through which the pandemic may have affected children's social and emotional development: the disruption to parents' experiences in the labour market created by lockdown restrictions.
Keywords: 330; Education and skills; Employment and income; Human capital; COVID-19; Human capital; Early childhood development; Labour supply and workforce; Family